Different dissipation potential and dietary risk assessment of tristyrylphenol ethoxylates in cowpea ecosystem in China - Li, Minjie; Wang, Qi; Li, Xiaohui; Yue, Ning; Jin, Maojun; Zheng, Lufei; Wang, Jing; Jin, Fen (Frontiers in Nutrition, 2022)
Tristyrylphenol ethoxylates (TSPEOn) are widely used as inert ingredients in pesticide formulations in the world. However, the information on the dissipation behavior of different homologs TSPEOn in agro-products is lacking. To investigate the dissipation behavior of TSPEOn, a cowpea field experiment treated with TSPEOn at different doses was carried out in Guangdong province, China. Different 24 TSPEO homologs were all detected in cowpea from the field terminal residue experiments, and the total concentrations of TSPEO homologs in cowpea were 40.0–1,374 μg/kg. The dissipation half-lives of 24 TSPEO homologs in soil were 1.51–2.35 times longer than those in cowpea. The long-chain homologs TSPEOn were dissipated faster than the short-chain homologs TSPEOn, suggesting a homolog-specific degradation of the TSPEOn in the cowpea ecosystem. The characteristic bimodal profiles of TSPEOn (n = 6–29) differing from that of the commercial TSPEOn were observed in the cowpea terminal residues experiment, indicating that the long-chain TSPEOn would degrade to short-chain TSPEOn in cowpea and soil. The acute and chronic dietary exposure risks of ΣTSPEOn in cowpea are within acceptable margins for human consumption across different ages and genders. But the health risks to children should be noticed in future.